Multi-layer temperature-regulating phase-change material coating and preparation method thereof

By applying a multi-layer temperature-regulating phase change material coating on textiles, using raw materials such as carbon fiber hybrids and nano-alumina sols, the problem of insufficient UV resistance under high-intensity sunlight irradiation is solved, and a higher anti-UV light and intensity effect is achieved.

CN119663646APending Publication Date: 2025-03-21SHANGHAI ALLTEX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411928823.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Current textiles made of temperature-controlled phase change materials have poor UV resistance under high-intensity sunlight, resulting in low practicality of textiles.

Method used

Multi-layer temperature-regulating phase change material coating, including aqueous resin, carbon fiber hybrids, composite fillers, paraffin, nano-alumina sol and other raw materials, are used to treat carbon fibers through ultrasonic assisted expansion and etching to increase their surface area and roughness, and nanomodified silica and ultraviolet absorbers are added to improve the UV resistance of the coating.

Benefits of technology

It significantly improves the UV resistance and strength of textiles, enhances the stability and flame retardant effect of coatings, and improves the overall performance of textiles.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a multilayer temperature-regulating phase-change material coating and a preparation method thereof, and particularly relates to the field of textile coatings, and the multilayer temperature-regulating phase-change material coating comprises the following raw materials: water-based resin, a carbon fiber hybrid, a composite filler, paraffin, nano-alumina sol, a surfactant, a dispersant, a defoaming agent, a coalescing agent and deionized water. According to the invention, the carbon fiber is expanded under the assistance of ultrasonic waves, so that the carbon fiber is widened, the surface area of the carbon fiber is increased, the surface roughness of the carbon fiber is increased by etching with an etching agent, and then isocyanate propyl triethoxy silane, nano-modified silicon dioxide, an ultraviolet light absorber and tetraethoxysilane are added, so that the surface roughness of the carbon fiber is increased; according to the present invention, the nanometer silicon dioxide is loaded on the surface of the carbon fiber, such that the nanometer modified silicon dioxide and the ultraviolet light absorber are loaded on the surface of the carbon fiber so as to improve the ultraviolet light resistance and the strength of the coating, and the vanillic aldehyde grafted chitosan is loaded on the nanometer silicon dioxide so as to improve the ultraviolet light absorption performance of the coating and improve the antibacterial property of the coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of textile coatings, and more specifically, to a multi-layer temperature-regulating phase-change material coating and a preparation method thereof. Background Art

[0002] Textiles are products made from processed and woven textile fibers. They can be divided into three categories according to their uses: clothing textiles, decorative textiles, and industrial products. As people's living standards continue to improve, their requirements for clothing products are getting higher and higher. In order to improve the comfort of wearing clothes, some clothing textiles are made of phase change materials.

[0003] Phase change material is a new type of environmentally friendly material that absorbs or releases heat in the form of latent heat by relying on its own reversible phase change when the external environment temperature changes. If the phase change material is mixed into the fiber or coated on the surface of the textile, the textile can be given an intelligent temperature regulation function. With the phase change of the phase change material contained in the textile, the textile can absorb heat from the environment and store it inside the textile or release the stored heat according to the change of the external environment temperature, forming a microclimate with a basically constant temperature around the textile. In this way, the temperature regulation function is realized and the comfort of textiles and clothing is improved. This type of textile product with automatic heat storage and regulation function is called intelligent temperature regulating textile, and the material used for intelligent temperature regulating textile is temperature regulating phase change material.

[0004] However, if the existing textiles made of temperature-regulating phase change materials are exposed to high-intensity sunlight for a long time during use, the anti-ultraviolet performance of the fabrics is poorly improved, resulting in low practicality of the temperature-regulating textiles. Summary of the invention

[0005] In order to overcome the above-mentioned defects of the prior art, an embodiment of the present invention provides a multi-layer temperature-adjusting phase change material coating and a preparation method thereof.

[0006] A multilayer temperature-regulating phase-change material coating comprises the following raw materials in parts by weight: 50-80 parts of water-based resin, 8-15 parts of carbon fiber hybrid, 3-8 parts of composite filler, 5-12 parts of paraffin wax, 5-10 parts of nano-alumina sol, 0.5-1.5 parts of surfactant, 0.2-0.8 parts of dispersant, 0.2-0.6 parts of defoaming agent, 0.3-0.6 parts of film-forming aid and 30-90 parts of deionized water.

[0007] In a preferred embodiment, the raw materials include the following parts by weight: 60-70 parts of water-based resin, 10-13 parts of carbon fiber hybrid, 5-6 parts of composite filler, 7-9 parts of paraffin wax, 7-8 parts of nano alumina sol, 0.8-1.2 parts of surfactant, 0.4-0.6 parts of dispersant, 0.3-0.5 parts of defoaming agent, 0.4-0.5 parts of film-forming aid and 50-70 parts of deionized water.

[0008] In a preferred embodiment, the raw materials include the following parts by weight: 65 parts of aqueous resin, 12 parts of carbon fiber hybrid, 5.5 parts of composite filler, 8 parts of paraffin, 7.5 parts of nano alumina sol, 1 part of surfactant, 0.5 part of dispersant, 0.4 part of defoaming agent, 0.45 part of film-forming aid and 60 parts of deionized water.

[0009] In a preferred embodiment, the water-based resin is one of water-based epoxy resin, water-based polyurethane, water-based fluorocarbon resin, and water-based acrylic resin, the surfactant is sodium dodecylbenzene sulfonate, the dispersant is barium stearate, the defoamer is an emulsified silicone oil defoamer, and the film-forming aid is propylene glycol methyl ether acetate.

[0010] In a preferred embodiment, the preparation method of the carbon fiber hybrid is as follows: the carbon fiber tow is expanded with the assistance of ultrasound, and then the carbon fiber tow is introduced into a reaction furnace through an electric transmission roller for electric heating, and then an etchant is added to etch the carbon fiber, and isocyanate propyl triethoxysilane is added to the etched carbon fiber, and after stirring and mixing evenly, nano-modified silica, ultraviolet light absorber and tetraethyl orthosilicate are added, and after mixing evenly, the carbon fiber hybrid is obtained by filtering and drying.

[0011] In a preferred embodiment, the frequency of ultrasonic assistance during expansion of the carbon fiber bundle is 0.1-0.3 MHz, the applied power is 0.5-0.8 W, the expansion time is 3-5 minutes, the etchant is a mixture of hydrogen and nitrogen, and the volume ratio of hydrogen to nitrogen is 1:(0.2-0.6).

[0012] In a preferred embodiment, the preparation method of the nano-modified silica is: adding nano-silica powder to an acetic acid aqueous solution, stirring evenly, adding vanillin-grafted chitosan, mixing evenly, and drying the nano-silica powder to obtain nano-modified silica.

[0013] In a preferred embodiment, the composite filler is a mixture of titanium dioxide, ceramic powder, glass beads, bentonite and calcium carbonate, and the mass ratio of titanium dioxide, ceramic powder, glass beads, bentonite and calcium carbonate is 1: (1.2-1.6): (0.3-0.7): (0.2-0.8): (0.8-1.2).

[0014] In a preferred embodiment, titanium dioxide, ceramic powder, glass beads, bentonite and calcium carbonate are weighed according to the above weight parts, stirred and mixed evenly, and then ultraviolet light absorber and silane coupling agent are added, soaked for 15-20 minutes under ultrasonic assistance, and then dried to obtain a composite filler.

[0015] The present invention also provides a method for preparing a multilayer temperature-adjusting phase change material coating, comprising the following steps:

[0016] Step 1: Put the weighed water-based resin, nano-alumina sol, paraffin and water into a mixing container, stir evenly, then add the composite filler and surfactant, and stir for 20-40 minutes at 35-45°C and with the aid of ultrasonic power of 300W-500W to obtain a premixed solution;

[0017] Step 2: Add the weighed carbon fiber hybrid, dispersant, defoamer, and film-forming aid into the premixed liquid in sequence, stir and mix evenly to prepare the coating liquid;

[0018] Step 3: Apply the coating liquid in step 2 on the textile, and form a multi-layer temperature-regulating phase change material coating on the textile after drying.

[0019] Technical effects and advantages of the present invention:

[0020] 1. A multilayer temperature-adjusting phase-change material coating prepared by the raw material formula of the present invention uses water-based resin as raw material, paraffin as phase-change material, and is added with raw materials such as carbon fiber hybrid, paraffin, composite filler, nano-alumina sol, etc. The carbon fiber is first expanded with the assistance of ultrasound to make the carbon fiber wider and increase the surface area of ​​the carbon fiber, and then etched with an etchant to increase the surface roughness of the carbon fiber, and then isocyanate propyl triethoxysilane, nano-modified silica, ultraviolet light absorber and tetraethyl orthosilicate are added to load the surface of the carbon fiber with nano-modified silica and ultraviolet light absorber, thereby improving the ultraviolet light resistance and strength of the coating, and the nano-silica is loaded with vanillin grafted chitosan, which can not only improve the ultraviolet light absorption performance of the coating, but also improve the antibacterial performance of the coating, and the added nano-alumina sol makes the coating more compatible, and the anti-ultraviolet light and hardness effects are improved;

[0021] 2. The composite filler in the present invention is a mixture of titanium dioxide, ceramic powder, glass beads, bentonite and calcium carbonate. The ceramic powder and glass beads have good stability, and the coating film formed has good stability. Titanium dioxide, bentonite and calcium carbonate have good flame retardant effect. Moreover, the composite filler is soaked in ultraviolet light absorber so that the outer side of the composite filler is coated with ultraviolet light absorber, so that the anti-ultraviolet light effect of the coating is better. DETAILED DESCRIPTION

[0022] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] Embodiment 1:

[0024] The present invention provides a multilayer temperature-regulating phase change material coating, comprising the following raw materials in parts by weight: 50 parts of water-based resin, 8 parts of carbon fiber hybrid, 3 parts of composite filler, 5 parts of paraffin, 5 parts of nano alumina sol, 0.5 parts of surfactant, 0.2 parts of dispersant, 0.2 parts of defoaming agent, 0.3 parts of film-forming aid and 30 parts of deionized water.

[0025] In a preferred embodiment, the water-based resin is water-based polyurethane, the surfactant is sodium dodecylbenzene sulfonate, the dispersant is barium stearate, the defoamer is an emulsified silicone oil defoamer, and the film-forming aid is propylene glycol methyl ether acetate. Specifically, in this application, the water-based polyurethane adopts the model AH-1604F water-based polyurethane produced by Anhui Dawei Huatai New Material Technology Co., Ltd., the sodium dodecylbenzene sulfonate adopts the sodium dodecylbenzene sulfonate with the classification number 25155-30-0 produced by Dechi Technology (Linyi) Co., Ltd., the barium stearate adopts the barium stearate with the classification number 6865-35-6 produced by Nantong Runfeng Petrochemical Co., Ltd., the emulsified silicone oil defoamer adopts the model B-0506 produced by Guangdong Zhongke Hongtai New Materials Co., Ltd., and the propylene glycol methyl ether acetate adopts the number 84540-57-8 produced by Zhengzhou Aikemu Chemical Co., Ltd. The ultraviolet light absorber used was produced by Hubei Yongkuo Technology Co., Ltd. and was numbered 131-56-6.

[0026] In a preferred embodiment, the preparation method of the carbon fiber hybrid is as follows: the carbon fiber tow is expanded with the assistance of ultrasound, and then the carbon fiber tow is introduced into a reaction furnace through an electric transmission roller for electric heating, and then an etchant is added to etch the carbon fiber, and isocyanate propyl triethoxysilane is added to the etched carbon fiber, and after stirring and mixing evenly, nano-modified silica, ultraviolet light absorber and tetraethyl orthosilicate are added, and after mixing evenly, the carbon fiber hybrid is obtained by filtering and drying.

[0027] In a preferred embodiment, the frequency of ultrasonic assistance during expansion of the carbon fiber bundle is 0.2 MHz, the applied power is 0.7 W, the expansion time is 4 minutes, the etchant is a mixture of hydrogen and nitrogen, and the volume ratio of hydrogen to nitrogen is 1:0.4.

[0028] In a preferred embodiment, the preparation method of the nano-modified silica is: adding nano-silica powder to an acetic acid aqueous solution, stirring evenly, adding vanillin-grafted chitosan, mixing evenly, and drying the nano-silica powder to obtain nano-modified silica.

[0029] In a preferred embodiment, the composite filler is a mixture of titanium dioxide, ceramic powder, glass microspheres, bentonite and calcium carbonate, and the mass ratio of the titanium dioxide, ceramic powder, glass microspheres, bentonite and calcium carbonate is 1:1.4:0.5:0.5:1.

[0030] In a preferred embodiment, titanium dioxide, ceramic powder, glass beads, bentonite and calcium carbonate are weighed according to the above weight parts, stirred and mixed evenly, and then ultraviolet light absorber and silane coupling agent are added, soaked for 18 minutes under ultrasonic assistance, and then dried to obtain a composite filler.

[0031] The present invention also provides a method for preparing a multilayer temperature-adjusting phase change material coating, comprising the following steps:

[0032] Step 1: Put the weighed water-based resin, nano-alumina sol, paraffin and water into a mixing container, stir evenly, then add the composite filler and surfactant, and stir for 30 minutes at 40° C. and with the assistance of an ultrasonic power of 400 W to obtain a premixed solution;

[0033] Step 2: Add the weighed carbon fiber hybrid, dispersant, defoamer, and film-forming aid into the premixed liquid in sequence, stir and mix evenly to prepare the coating liquid;

[0034] Step 3: Apply the coating liquid in step 2 on the textile, and form a multi-layer temperature-regulating phase change material coating on the textile after drying.

[0035] Embodiment 2:

[0036] Different from Example 1, the multilayer temperature-regulating phase change material coating includes the following raw materials in parts by weight: 65 parts of aqueous resin, 12 parts of carbon fiber hybrid, 5.5 parts of composite filler, 8 parts of paraffin, 7.5 parts of nano alumina sol, 1 part of surfactant, 0.5 part of dispersant, 0.4 part of defoaming agent, 0.45 part of film-forming aid and 60 parts of deionized water.

[0037] Embodiment 3:

[0038] Different from Examples 1-2, the multilayer temperature-regulating phase change material coating includes the following raw materials in parts by weight: 80 parts of aqueous resin, 15 parts of carbon fiber hybrid, 8 parts of composite filler, 12 parts of paraffin, 10 parts of nano alumina sol, 1.5 parts of surfactant, 0.8 parts of dispersant, 0.6 parts of defoaming agent, 0.6 parts of film-forming aid and 90 parts of deionized water.

[0039] Embodiment 4:

[0040] The present invention provides a multilayer temperature-regulating phase change material coating, comprising the following raw materials in parts by weight: 50 parts of aqueous resin, 8 parts of carbon fiber, 3 parts of composite filler, 5 parts of paraffin, 5 parts of nano alumina sol, 0.5 parts of surfactant, 0.2 parts of dispersant, 0.2 parts of defoaming agent, 0.3 parts of film-forming aid and 30 parts of deionized water.

[0041] In a preferred embodiment, the water-based resin is water-based polyurethane, the surfactant is sodium dodecylbenzene sulfonate, the dispersant is barium stearate, the defoamer is an emulsified silicone oil defoamer, and the film-forming aid is propylene glycol methyl ether acetate. Specifically, in this application, the water-based polyurethane adopts the model AH-1604F water-based polyurethane produced by Anhui Dawei Huatai New Material Technology Co., Ltd., the sodium dodecylbenzene sulfonate adopts the sodium dodecylbenzene sulfonate with the classification number 25155-30-0 produced by Dechi Technology (Linyi) Co., Ltd., the barium stearate adopts the barium stearate with the classification number 6865-35-6 produced by Nantong Runfeng Petrochemical Co., Ltd., the emulsified silicone oil defoamer adopts the model B-0506 produced by Guangdong Zhongke Hongtai New Materials Co., Ltd., and the propylene glycol methyl ether acetate adopts the number 84540-57-8 produced by Zhengzhou Aikemu Chemical Co., Ltd. The ultraviolet light absorber used was produced by Hubei Yongkuo Technology Co., Ltd. and was numbered 131-56-6.

[0042] In a preferred embodiment, the composite filler is a mixture of titanium dioxide, ceramic powder, glass microspheres, bentonite and calcium carbonate, and the mass ratio of the titanium dioxide, ceramic powder, glass microspheres, bentonite and calcium carbonate is 1:1.4:0.5:0.5:1.

[0043] In a preferred embodiment, titanium dioxide, ceramic powder, glass beads, bentonite and calcium carbonate are weighed according to the above weight parts, stirred and mixed evenly, and then ultraviolet light absorber and silane coupling agent are added, soaked for 18 minutes under ultrasonic assistance, and then dried to obtain a composite filler.

[0044] The present invention also provides a method for preparing a multilayer temperature-adjusting phase change material coating, comprising the following steps:

[0045] Step 1: Put the weighed water-based resin, nano-alumina sol, paraffin and water into a mixing container, stir evenly, then add the composite filler and surfactant, and stir for 30 minutes at 40° C. and with the assistance of an ultrasonic power of 400 W to obtain a premixed solution;

[0046] Step 2: Add the weighed carbon fiber, dispersant, defoamer, and film-forming aid into the premixed liquid in sequence, stir and mix evenly to prepare the coating liquid;

[0047] Step 3: Apply the coating liquid in step 2 on the textile, and form a multi-layer temperature-regulating phase change material coating on the textile after drying.

[0048] Embodiment 5:

[0049] The present invention provides a multilayer temperature-regulating phase change material coating, comprising the following raw materials in parts by weight: 50 parts of aqueous resin, 8 parts of carbon fiber hybrid, 3 parts of filler, 5 parts of paraffin, 5 parts of nano alumina sol, 0.5 parts of surfactant, 0.2 parts of dispersant, 0.2 parts of defoaming agent, 0.3 parts of film-forming aid and 30 parts of deionized water.

[0050] In a preferred embodiment, the water-based resin is water-based polyurethane, the surfactant is sodium dodecylbenzene sulfonate, the dispersant is barium stearate, the defoamer is an emulsified silicone oil defoamer, and the film-forming aid is propylene glycol methyl ether acetate. Specifically, in this application, the water-based polyurethane adopts the model AH-1604F water-based polyurethane produced by Anhui Dawei Huatai New Material Technology Co., Ltd., the sodium dodecylbenzene sulfonate adopts the sodium dodecylbenzene sulfonate with the classification number 25155-30-0 produced by Dechi Technology (Linyi) Co., Ltd., the barium stearate adopts the barium stearate with the classification number 6865-35-6 produced by Nantong Runfeng Petrochemical Co., Ltd., the emulsified silicone oil defoamer adopts the model B-0506 produced by Guangdong Zhongke Hongtai New Materials Co., Ltd., and the propylene glycol methyl ether acetate adopts the number 84540-57-8 produced by Zhengzhou Aikemu Chemical Co., Ltd. The ultraviolet light absorber used was produced by Hubei Yongkuo Technology Co., Ltd. and was numbered 131-56-6.

[0051] In a preferred embodiment, the preparation method of the carbon fiber hybrid is as follows: the carbon fiber tow is expanded with the assistance of ultrasound, and then the carbon fiber tow is introduced into a reaction furnace through an electric transmission roller for electric heating, and then an etchant is added to etch the carbon fiber, and isocyanate propyl triethoxysilane is added to the etched carbon fiber, and after stirring and mixing evenly, nano-modified silica, ultraviolet light absorber and tetraethyl orthosilicate are added, and after mixing evenly, the carbon fiber hybrid is obtained by filtering and drying.

[0052] In a preferred embodiment, the frequency of ultrasonic assistance during expansion of the carbon fiber bundle is 0.2 MHz, the applied power is 0.7 W, the expansion time is 4 minutes, the etchant is a mixture of hydrogen and nitrogen, and the volume ratio of hydrogen to nitrogen is 1:0.4.

[0053] In a preferred embodiment, the preparation method of the nano-modified silica is: adding nano-silica powder to an acetic acid aqueous solution, stirring evenly, adding vanillin-grafted chitosan, mixing evenly, and drying the nano-silica powder to obtain nano-modified silica.

[0054] In a preferred embodiment, the filler is titanium dioxide.

[0055] The present invention also provides a method for preparing a multilayer temperature-adjusting phase change material coating, comprising the following steps:

[0056] Step 1: Put the weighed water-based resin, nano-alumina sol, paraffin and water into a mixing container, stir evenly, then add filler and surfactant, and stir for 30 minutes at 40°C and with the assistance of ultrasonic power of 400W to obtain a premixed solution;

[0057] Step 2: Add the weighed carbon fiber hybrid, dispersant, defoamer, and film-forming aid into the premixed liquid in sequence, stir and mix evenly to prepare the coating liquid;

[0058] Step 3: Apply the coating liquid in step 2 on the textile, and form a multi-layer temperature-regulating phase change material coating on the textile after drying.

[0059] Comparative Example:

[0060] The present invention provides a multilayer temperature-regulating phase-change material coating, comprising the following raw materials in parts by weight: 50 parts of aqueous resin, 3 parts of filler, 5 parts of paraffin, 5 parts of nano-alumina sol, 0.5 parts of surfactant, 0.2 parts of dispersant, 0.2 parts of defoaming agent, 0.3 parts of film-forming aid and 30 parts of deionized water.

[0061] In a preferred embodiment, the water-based resin is water-based polyurethane, the surfactant is sodium dodecylbenzene sulfonate, the dispersant is barium stearate, the defoamer is an emulsified silicone oil defoamer, and the film-forming aid is propylene glycol methyl ether acetate. Specifically, in this application, the water-based polyurethane adopts the model AH-1604F water-based polyurethane produced by Anhui Dawei Huatai New Material Technology Co., Ltd., the sodium dodecylbenzene sulfonate adopts the sodium dodecylbenzene sulfonate with the classification number 25155-30-0 produced by Dechi Technology (Linyi) Co., Ltd., the barium stearate adopts the barium stearate with the classification number 6865-35-6 produced by Nantong Runfeng Petrochemical Co., Ltd., the emulsified silicone oil defoamer adopts the model B-0506 produced by Guangdong Zhongke Hongtai New Materials Co., Ltd., and the propylene glycol methyl ether acetate adopts the number 84540-57-8 produced by Zhengzhou Aikemu Chemical Co., Ltd. The ultraviolet light absorber used was produced by Hubei Yongkuo Technology Co., Ltd. and was numbered 131-56-6.

[0062] In a preferred embodiment, the composite filler is titanium dioxide.

[0063] The present invention also provides a method for preparing a multilayer temperature-adjusting phase change material coating, comprising the following steps:

[0064] Step 1: Put the weighed water-based resin, nano-alumina sol, paraffin and water into a mixing container, stir evenly, then add filler and surfactant, and stir for 30 minutes at 40°C and with the assistance of ultrasonic power of 400W to obtain a premixed solution;

[0065] Step 2: Add the weighed dispersant, defoamer and film-forming aid into the premixed liquid in sequence, stir and mix evenly to prepare the coating liquid;

[0066] Step 3: Apply the coating liquid in step 2 on the textile, and form a multi-layer temperature-regulating phase change material coating on the textile after drying.

[0067] The multilayer temperature-adjusting phase change material coating in the comparative example and the embodiment of the present invention was tested and processed:

[0068] Anti-ultraviolet performance: The coating adhesive prepared in each embodiment and comparative example was coated on the same kind of textile, dried and fixed, and the anti-ultraviolet performance of the textile was tested with reference to GB / T18830-2002, and characterized by the UPF value;

[0069] Anti-pollution performance: Under sufficient light, the coating adhesive prepared in each embodiment and comparative example was coated on the same kind of textile, dried and fixed, and the anti-pollution performance of the textile was characterized with reference to GB / T30159.1-2013.

[0070] The results are shown in Table 1:

[0071] UPF Anti-pollution Example 1 243 5 Example 2 255 5 Example 3 248 5 Example 4 196 4 Example 5 220 5 Comparative Example 150 3

[0072] Table 1

[0073] It can be seen from the above table that the multilayer temperature-regulating phase change material coating of the present invention has good anti-ultraviolet and anti-pollution effects, while Example 4 uses carbon fiber instead of carbon fiber hybrid, and its anti-ultraviolet and anti-pollution effects are reduced, and Example 5 uses pure titanium dioxide filler, and its anti-ultraviolet effect is slightly reduced. Therefore, the carbon fiber of the present invention is first expanded with the assistance of ultrasound to make the carbon fiber wider and increase the surface area of ​​the carbon fiber, and then etched with an etchant to increase the surface roughness of the carbon fiber, and then isocyanate propyl triethoxysilane, nano-modified silica, ultraviolet absorber and tetraethyl orthosilicate are added to load the surface of the carbon fiber with nano-modified silica and ultraviolet absorber, thereby improving the ultraviolet resistance of the coating. The invention has the advantages of good external light performance and strength, and the vanillin grafted chitosan is loaded on the nano silicon dioxide, which can not only improve the absorption performance of the coating to ultraviolet light, but also improve the antibacterial performance of the coating, and the added nano alumina sol makes the coating have better compatibility, and the anti-ultraviolet light and hardness effects are improved; the composite filler in the invention is a mixture of titanium dioxide, ceramic powder, glass microbeads, bentonite and calcium carbonate, the ceramic powder and glass microbeads have good stability, the formed coating film has good stability, titanium dioxide, bentonite and calcium carbonate have good flame retardant effect, and the composite filler is soaked in ultraviolet light absorber, so that the outer side of the composite filler is coated with ultraviolet light absorber, so that the anti-ultraviolet light effect of the coating is better.

[0074] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A multi-layer temperature-adjusting phase change material coating, characterized in that: The invention comprises the following raw materials in parts by weight: 50-80 parts of water-based resin, 8-15 parts of carbon fiber hybrid, 3-8 parts of composite filler, 5-12 parts of paraffin wax, 5-10 parts of nano alumina sol, 0.5-1.5 parts of surfactant, 0.2-0.8 parts of dispersant, 0.2-0.6 parts of defoaming agent, 0.3-0.6 parts of film-forming aid and 30-90 parts of deionized water.

2. The multi-layer temperature-adjusting phase change material coating according to claim 1, characterized in that: The invention comprises the following raw materials in parts by weight: 60-70 parts of water-based resin, 10-13 parts of carbon fiber hybrid, 5-6 parts of composite filler, 7-9 parts of paraffin wax, 7-8 parts of nano alumina sol, 0.8-1.2 parts of surfactant, 0.4-0.6 parts of dispersant, 0.3-0.5 parts of defoaming agent, 0.4-0.5 parts of film-forming aid and 50-70 parts of deionized water.

3. The multi-layer temperature-adjusting phase change material coating according to claim 1, characterized in that: The invention comprises the following raw materials in parts by weight: 65 parts of water-based resin, 12 parts of carbon fiber hybrid, 5.5 parts of composite filler, 8 parts of paraffin wax, 7.5 parts of nano alumina sol, 1 part of surfactant, 0.5 part of dispersant, 0.4 part of defoamer, 0.45 part of film-forming aid and 60 parts of deionized water.

4. The multi-layer temperature-adjusting phase change material coating according to claim 1, characterized in that: The water-based resin is one of water-based epoxy resin, water-based polyurethane, water-based fluorocarbon resin, and water-based acrylic resin; the surfactant is sodium dodecylbenzene sulfonate; the dispersant is barium stearate; the defoamer is an emulsified silicone oil defoamer; and the film-forming aid is propylene glycol methyl ether acetate.

5. The multi-layer temperature-adjusting phase change material coating according to claim 1, characterized in that: The preparation method of the carbon fiber hybrid is as follows: the carbon fiber tow is expanded with the assistance of ultrasound, and then the carbon fiber tow is introduced into a reaction furnace through an electric transmission roller for electric heating, and then an etchant is added to perform etching, and isocyanate propyl triethoxysilane is added to the etched carbon fiber, and after stirring and mixing, nano-modified silica, ultraviolet light absorber and ethyl orthosilicate are added, and after mixing, the carbon fiber hybrid is obtained by filtering and drying.

6. The multi-layer temperature-adjusting phase change material coating according to claim 5, characterized in that: The frequency of ultrasonic assistance during the expansion of the carbon fiber bundle is 0.1-0.3 MHz, the applied power is 0.5-0.8 W, the expansion time is 3-5 minutes, the etchant is a mixture of hydrogen and nitrogen, and the volume ratio of hydrogen to nitrogen is 1:(0.2-0.6).

7. The multi-layer temperature-adjusting phase change material coating according to claim 5, characterized in that: The preparation method of the nano-modified silicon dioxide comprises the following steps: adding nano-silicon dioxide powder to an acetic acid aqueous solution, stirring evenly, adding vanillin grafted chitosan, mixing evenly, and drying the nano-silicon dioxide powder to obtain the nano-modified silicon dioxide.

8. The multi-layer temperature-adjusting phase change material coating according to claim 7, characterized in that: The composite filler is a mixture of titanium dioxide, ceramic powder, glass microspheres, bentonite and calcium carbonate, and the mass ratio of the titanium dioxide, ceramic powder, glass microspheres, bentonite and calcium carbonate is 1: (1.2-1.6): (0.3-0.7): (0.2-0.8): (0.8-1.2).

9. The multi-layer temperature-adjusting phase change material coating according to claim 8, characterized in that: The preparation method of the composite filler is as follows: titanium dioxide, ceramic powder, glass microspheres, bentonite and calcium carbonate are weighed according to the above weight parts, ultraviolet light absorber and silane coupling agent are added after stirring and mixing evenly, soaking for 15-20 minutes under the assistance of ultrasonic wave, and then drying to obtain the composite filler.

10. A method for preparing a multi-layer temperature-adjusting phase change material coating according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step 1: Put the weighed water-based resin, paraffin, nano-alumina sol and water into a mixing container, stir evenly, then add the composite filler and surfactant, and stir for 20-40 minutes at 35-45° C. and with the aid of ultrasonic power of 300W-500W to obtain a premixed solution; Step 2: Add the weighed carbon fiber hybrid, dispersant, defoamer, and film-forming aid into the premixed liquid in sequence, stir and mix evenly to prepare the coating liquid; Step 3: Apply the coating liquid in step 2 on the textile, and form a multi-layer temperature-regulating phase change material coating on the textile after drying.